2006
DOI: 10.1037/0022-006x.74.5.898
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing therapy for veterans with military-related posttraumatic stress disorder.

Abstract: Sixty veterans (54 men, 6 women) with chronic military-related posttraumatic stress disorder (PTSD) participated in a wait-list controlled trial of cognitive processing therapy (CPT). The overall dropout rate was 16.6% (20% from CPT, 13% from waiting list). Random regression analyses of the intention-to-treat sample revealed significant improvements in PTSD and comorbid symptoms in the CPT condition compared with the wait-list condition. Forty percent of the intention-to-treat sample receiving CPT did not meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
559
5
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 785 publications
(607 citation statements)
references
References 56 publications
38
559
5
5
Order By: Relevance
“…Study results demonstrated that all outcome variables (PTSD symptoms, depression symptoms, occupational performance, and satisfaction with occupational performance) significantly improved over the course of residential treatment. Furthermore, reductions in all outcome variables were clinically significant as reflected in CAPS score changes of ³15 and PCL-S score changes of ³10 (Monson et al, 2006), BDI-II average score changes from severe (29-63) to mild (14-19) depression (Beck et al, 1996), and changes in COPM levels of ³2 (Law et al, 1994;Phipps & Richardson, 2007). In sum, changes were both statistically significant and clinically meaningful.…”
Section: Discussionmentioning
confidence: 69%
“…Study results demonstrated that all outcome variables (PTSD symptoms, depression symptoms, occupational performance, and satisfaction with occupational performance) significantly improved over the course of residential treatment. Furthermore, reductions in all outcome variables were clinically significant as reflected in CAPS score changes of ³15 and PCL-S score changes of ³10 (Monson et al, 2006), BDI-II average score changes from severe (29-63) to mild (14-19) depression (Beck et al, 1996), and changes in COPM levels of ³2 (Law et al, 1994;Phipps & Richardson, 2007). In sum, changes were both statistically significant and clinically meaningful.…”
Section: Discussionmentioning
confidence: 69%
“…Additional analyses indicated that CPT resulted in small but positive effect-size differences for PTSD, depression, and guilt measures at posttreatment, 3 months, and 9 months, indicating modestly greater symptomatic improvement relative to the participants in the PE condition. Monson et al conducted an RCT comparing CPT with a wait-list control in Veterans, primarily Vietnam war Veterans who had chronic military-related PTSD [3]. The Veterans who received CPT had a significant reduction in severity of PTSD symptoms over time as compared with the wait-list control group (g = 1.01-1.12).…”
Section: Evidence Base For Cognitive Process-ing Therapymentioning
confidence: 99%
“…Prolonged Exposure therapy (PE; Foa et al, 1999;Foa et al, 2005;Schnurr et al, 2007) and Cognitive Processing Therapy (CPT; Resick et al, 2008;Resick, Nishith, Weaver, Astin, & Feurer, 2002;Resick & Schnicke, 1992;Monson et al, 2006), emerged from the past decade of clinical research as effective, first-line treatments for PTSD (Bisson, Ehlers, Mathews, Pilling, Richards, & Turner, 2007; Institute of Medicine, 2007; VA/DoD Clinical Practice Guideline for Management of Post-Traumatic Stress, 2003). PE and CPT typically are delivered in weekly 60-to 90-min individual sessions over 10 to 12 weeks in specialty mental health clinics.…”
mentioning
confidence: 99%